Migration of Jewish "Displaced Persons" from Europe to Australia after the Second World War: Revisiting the Question of Discrimination and Numbers. (28th September 2021) - Fitzpatrick, Sheila
Abstract : Post‐war Jewish immigration from Europe to Australia has been much discussed in the scholarship, primarily with reference to the question of discriminatory (anti‐semitic) intention on the part of the Australian government and the Department of Immigration bureaucracy. The assumption has often been made that the existence of discriminatory policy and practices necessarily led to a reduction in the number of Jewish migrants entering Australia. Using new data on Jewish entrants under the Mass Resettlement programme (1947–51) and under individual sponsorship on landing permits, as well as material from the archives of the International Refugee Organization which administered the Mass Resettlement programme, this article revisits the related questions of discriminatory intentions and quantitative outcomes, concluding that discriminatory intent, while stimulating evasive strategies of resistance on the part of individuals and institutions, does not necessarily result in significant reduction in the rate of entry of the migrants who are the object of discrimination.